Digitisation and European copyright protection: Between economic challenges and stakeholder interests - Marie Möller (Institut der deutschen Wirtschaft (IW), 2016)
The increasing digitisation necessitates amendments to copyright protection. Both the European Parliament and the European Commission have now presented proposals addressing this issue. This is necessary because the way in which creative goods are produced and distributed has been changed dramatically by digital technologies and the spread of the internet. One challenge that arises from this is the application of the Country of Origin principle and the resulting practice of geo-blocking. The resale of digital good represents another challenge in this context. Individual stakeholders have different interests with regard to copyright protection in a digital economy. For example, consumers (private or institutional users) have an interest in the resale of digital goods, whereas suppliers (authors, collecting societies, publishers) do not. The EU Parliament's proposal for copyright reform sides more with the suppliers than with the consumers. Future policy at EU level should attempt to create a clear, comprehensible legal framework and thus establish legal certainty. – – Die fortschreitende Digitalisierung macht Anpassungen des Urheberschutzes erforderlich. Sowohl das Europäische Parlament als auch die Europäische Kommission haben dazu inzwischen Vorschläge vorgelegt. Hintergrund ist, dass die Art, wie kreative Güter produziert und verbreitet werden, durch digitale Technologien und die Verbreitung des Internet stark verändert wurde. Eine Herausforderung, die sich dadurch ergibt, ist die Anwendung des Ursprungslandprinzips und die daraus resultierende Praxis des Geo-Blocking. Eine weitere Herausforderung besteht in Bezug auf die Frage der Weiterveräußerung digitaler Güter. Die einzelnen Stakeholder haben unterschiedliche Interessen bezüglich der Problemfelder. So zeigt sich beispielsweise, dass die Konsumenten (private oder institutionelle Nutzer) ein Interesse an der Weiterveräußerung digitaler Güter haben, die Anbieterseite (Autoren, Verwertungsgesellschaften, Verleger) dieses hingegen nicht hat. Der Parlamentsvorschlag zur Urheberrechtsreform entspricht eher den gewünschten politischen Maßnahmen der Anbieter als denen der Nachfrager. Bei zukünftigen Entscheidungen auf EU-Ebene sollte versucht werden, einen nachvollziehbaren Rechtsrahmen zu schaffen und somit Rechtssicherheit zu erzeugen.
Keywords: O34; O33; K00; 330